Violence against women at work: regulation, perception and responsibility of entrepreneur - Martín Izquierdo, Elena (Universidad de Sonora, 2021)
Violence against women in society has become widespread and transcends differences in income, social classes and cultures and must be countered by urgent and effective measures to eliminate its impact. It is important to highlight the importance for companies of conveying an image of trust and commitment to society, since, the imperatives of business success, are largely the social externalities it causes. A process of redefining rights and policies is needed by empowering women comprehensively in the workplace, thus contributing to the fulfillment of promises of sustainability, peace and human progress.